The distinction between Church and State: the ideological roots of a Category-Mistake. - Strauss, DFM (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
Against the background of the rise of the classical Greek ideal of the life-encompassing polis (city state) and the absorption of this classical state ideology within the medieval ecclesiastically unified culture (the ideal of the “Corpus Christianum” as the “societas perfecta” – incorporating a brief assessment of the ideas of Augustine and Thomas Aquinas) attention is given to the emergence, since the Renaissance, of the state and church through a process of historical differentiation. This process experienced the mixed influence both of modern Humanism and Protestantism, while the latter continued to struggle with the after-effects of the dualistic world view of Scholasticism. The implications of the Biblical creation motive for an understanding of the unity and goodness of life is then articulated with the aim to highlight the distinctness of structure and direction. The state as a legal community and the nature of a faith community ought to be understood in terms of the typical structural principles (type-laws) making these different societal entities possible in the first place. Only when attention is given to the application or “positivisation” of the type-law of a faith community is it possible to speak about the church as something that is Christian by definition. However, the practice to distinguish between church and state in the final analysis turns out to be a subtle after-effect of an ideological “two terrain” distortion of the unity and goodness of God’s creation – leading to the category-mistake that compares apples with pears.